Potential animal reservoirs (dogs and bats) of human visceral leishmaniasis due to Leishmania infantum in French Guiana. - Hacène Medkour; Bernard Davoust; François Dulieu; Laurent Maurizi; Thierry Lamour; Jean-Lou Marié; Oleg Mediannikov (Public Library of Science (PLoS), 2019)
In French Guiana, cutaneous leishmaniasis is highly endemic, whereas no autochthonous case of visceral leishmaniasis have been reported so far. However, due to its proximity to Brazil which is highly endemic for visceral leishmaniasis, and the high transboundary population flow, an epidemiological challenge could arise at any time. As an overseas department and region and the largest outermost region of the European Union, epidemiological surveillance of visceral leishmaniasis is of great importance. Our study aimed to investigate the presence of Leishmania spp. in domestic (dogs) and sylvatic (bats) animals from French Guiana. Over the 2008-2018 period, samples from 349 animals were collected. They included blood from 179 autochthonous dogs and 59 bats, spleen samples from 33 bats and, blood from 78 military working dogs (MWD) collected before their departure from continental France and at the end of their four-month stay in French Guiana. Samples were screened using real-time polymerase chain reaction (qPCR) assays targeting Leishmania DNA followed by sequencing of 18S rRNA, kDNA and ITS2 genes. L. infantum was detected in 2.3% (8/349) of animals with 1.7% (3/179) of autochthonous dogs, 5.1% (4/78) of MWD returning from French Guiana, whereas they were negative before their departure. One of them dates back to 2012. All these dogs were positive for serological tests. In addition, L. infantum DNA was detectable in one bat spleen sample, belonging to Carollia perspicillata species. We report here for the first time an infection with L. infantum in dogs and bat from French Guiana. Our results suggest the existence of potential reservoir and transmission cycle for visceral leishmaniasis, at least since 2012, which was unknown in this territory until now. Further studies are needed to determine how these animals were infected and which vectors are involved in the transmission in this area.